People living with HIV experience in dealing with HIV/AIDS symptoms - Rahmi Muthia; Fitri Mailani; Dally Rahman; Emil Huriani; Khatijah Lim Abdullah (STIKep PPNI Jawa Barat, 2021)
Aims : This study aimed to explore the PLWH live experience in dealing with HIV / AIDS symptoms. Design : This study applied qualitative method. Methdos : This study used descriptive explorative to explore the HIV symptoms experiences of PLWH in Padang West Sumatera, Indonesia. We conducted an unstructured interview among purposively sample PLWH. Inclusion criteria for participation were being male or female PLWH, residing in Padang, and age over 18 years. Data saturation was reached after the completion of 9 interviews. Content analysis was used to analyze and interpret qualitative data. Results : The following themes emerged from the data: (a) face troublesome symptoms, (b) health literacy in HIV care, and (c) make efforts to heal. Conclusions : PLWH experience HIV symptoms, continue to adapt and learn. The information about HIV symptoms experiences can facilitate caregiver to plan nursing care, identify education needs to help PLWH dealing with symptoms of HIV. This research can be the basis for conducting further research on how to manage the symptoms of HIV.